2020
DOI: 10.1038/s41598-020-77425-z
|View full text |Cite
|
Sign up to set email alerts
|

Acral lentiginous melanoma in situ: dermoscopic features and management strategy

Abstract: Diagnosis of acral lentiginous melanoma in situ (ALMIS) is challenging. However, data regarding ALMIS are limited in the literature. The aim of this study was to investigate the clinical and dermoscopic features of ALMIS on palmoplantar surfaces. Patients with ALMIS and available dermoscopic images were retrospectively reviewed at our institution between January 2013 and February 2020. Clinical and dermoscopic features were analysed and compared between small (< 15 mm) and large (≥ 15 mm) ALMIS. Twenty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…ALM is the main type of melanoma in colored races. 31 Studies have found that ALM occurs less frequently in white people, accounting for only 4%–10% of skin melanoma, but it has a higher proportion in Hispanic, Asian, African, and other people of color. 32–35 Of note, the study also found that being unmarried and DSW were risk factors affecting the prognosis of patients with ALM.…”
Section: Discussionmentioning
confidence: 99%
“…ALM is the main type of melanoma in colored races. 31 Studies have found that ALM occurs less frequently in white people, accounting for only 4%–10% of skin melanoma, but it has a higher proportion in Hispanic, Asian, African, and other people of color. 32–35 Of note, the study also found that being unmarried and DSW were risk factors affecting the prognosis of patients with ALM.…”
Section: Discussionmentioning
confidence: 99%
“…26 The parallel ridge pattern (PRP) has been described as the most characteristic pattern of ALM, although its absence does not exclude a possible diagnosis of ALM. 27,28 Parallel ridge pattern presents as pigment along the ridges. 29 The sensitivity and specificity of PRP in ALM are 86.4% and 99%, respectively.…”
Section: Dermoscopymentioning
confidence: 99%
“…30 By contrast, benign lesions display benign patterns throughout the lesion. Advanced ALM may also show non-site-specific dermoscopic features of melanoma, such as irregular dots and globules, irregular streaks and pseudopods, regression structures, blue-white veil, and atypical vessels 27,28 (see Supplemental Digital Content 1, Table 3, http://links.lww.com/DSS/B301).…”
Section: Dermoscopymentioning
confidence: 99%
“…Based on these characteristic dermoscopic findings, in 2007 our group proposed a dermoscopic 3-step algorithm for the management of acral melanocytic lesions [3] and then, revised it in 2011 [4]. Recently, several studies were reported which examined utility of the 3-step algorithm [5][6][7]. In these studies, the 3-step algorithm generally worked well, however, in one study, the algorithm missed one lesion of AM, 0.5 mm in Breslow thickness.…”
Section: Re-revisionmentioning
confidence: 99%